Penerapan Asesmen Diagnostik Non Kognitif Sebagai Upaya Analisis Kebutuhan Siswa - Triani, Ririn; Mariyani, Mariyani (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
Evaluation is an assessment carried out to review the extent to which a program has been achieved and is also used as a consideration for the next steps. One of the evaluations (selections) recommended in the independent curriculum is a diagnostic assessment consisting of cognitive and non-cognitive diagnostic assessments. Cognitive diagnostic assessments are carried out by giving several questions to students at the beginning of learning activities. While non-cognitive diagnostic assessments are carried out in accordance with the policies or strategies of each school. Thus, this study aims to determine the implementation of non-cognitive diagnostic assessments at SMP Negeri 1 Indralaya. This study uses a qualitative approach in descriptive form with a case study method. The data collection technique used in this study is Triangulation which consists of interviews, observations and documentation. The sampling technique used in this study is the purposive sampling technique. Based on the results of the research analysis, it was found that the implementation of non-cognitive diagnostic assessments at SMP Negeri 1 Indralaya was in the very good category with the help of the use of written questionnaires that must be filled out by students and supervised by teachers. This is done to make it easier for teachers to identify the needs and problems of students in implementing learning. However, there are limitations in this study, namely that the context discussed is only limited to the implementation of non-cognitive diagnostic assessments at SMP Negeri 1 Indralaya so that the results cannot be generalized to other institutions because each educational institution has different policies regarding the implementation of non-cognitive diagnostic assessments.